Peningkatan Pemahaman Bela Negara Terhadap NKRI Pada Masyarakat RT03/RW17 Dusun 3 Bencah Limbat Di Desa Pandau Jaya Kecamatan Siak Hulu Kabupaten Kampar (UIR PRESS, 2023)
National Defense is a concept about the patriotism of a person or all components of a country. Physically, it is defined as an effort to defend against all forms of threats, disturbances, obstacles and challenges to the existence of the country. Non-physically, defending the country is defined as an active role in advancing the nation and state, either through education, morals, social, and so on. The problems that occur among the people of Bencah Limbat Hamlet and we think also in all regions in Indonesia, the public's understanding regarding National Defense is still very lacking and the value of Love for the Republic of Indonesia is starting to be degraded, many people think that the action of Defending the Country is just Military Service, but there are many other things including defensive actions. country. We want to emphasize this understanding to the Indonesian people, especially the people of RT03 Bencah Limbat Hamlet, Pandau Jaya Village, Kab. Kampar, Riau. The solution is of course to go directly into the community, carry out outreach, give the public an understanding of the nature of National Defense actions, how people can understand that National Defense is not a very difficult thing, it is not something scary, in fact there are many small things that can be done. as a form of defending the country, a small example is creating a safe social environment, mutual tolerance, mutual cooperation, so that these small things can foster a sense of patriotism towards people as Indonesian citizens.